Nanostructured Biomaterials for Bone Regeneration - Lyons, Joseph G.; Plantz, Mark A.; Hsu, Wellington K.; Hsu, Erin L.; Minardi, Silvia (Frontiers in Bioengineering and Biotechnology, 2020)
This review article addresses the various aspects of nano-biomaterials used in or being pursued for the purpose of promoting bone regeneration. In the last decade, significant growth in the fields of polymer sciences, nanotechnology, and biotechnology has resulted in the development of new nano-biomaterials. These are extensively explored as drug delivery carriers and as implantable devices. At the interface of nanomaterials and biological systems, the organic and synthetic worlds have merged over the past two decades, forming a new scientific field incorporating nano material design for biological applications. For this field to evolve, there is a need to understand the dynamic forces and molecular components that shape these interactions and influence function, while also considering safety. While there is still much to learn about the bio physicochemical interactions at the interface, we are at a point where pockets of accumulated knowledge can provide a conceptual framework to guide further exploration and inform future product development. This review is intended as a resource for academics, scientists, and physicians working in the field of orthopaedics and bone repair.